The Psychedelic Renaissance in Clinical Research: A Bibliometric Analysis of Three Decades of Human Studies with Psychedelics. Issue 1 (1st January 2023) - Hadar, Aviad; David, Jonathan; Shalit, Nadav; Roseman, Leor; Gross, Raz; Sessa, Ben; Lev-Ran, Shaul
ABSTRACT: Psychedelics were used in the treatment of psychiatric conditions prior to their prohibition in the late 1960s. In the past three decades, there is a revived research interest in the therapeutic potential of psychedelic drugs with expected FDA approvals for treatment of various conditions. Given the exponential scientific growth of this field, we sought to characterize, analyze, and visualize trends in its top-cited articles. Bibliometric analyses are quantitative approaches to characterize a scientific field, including evaluation of the impact of academic literature. The bibliometric analysis and visualizations were conducted with R-tools for comprehensive science mapping. The top-cited 100 articles were cited between 82 and 668 times (median 125; mean 158). Fifty-four percent of the T100 articles were produced in the past decade (2010–2020). Network and author impact analysis highlighted key figures and primary collaboration networks within the top 100 publications. UK, USA, Switzerland, Spain, and Brazil lead the field. Results are discussed in terms of research growth, access, diversity, and the distribution of knowledge and experience in the field. These aggregated data and insights on the second wave of psychedelic research facilitate research evaluation, data-driven funding policies, and a practical map for researchers and clinicians entering the field.